2011
DOI: 10.1167/iovs.10-5885
|View full text |Cite
|
Sign up to set email alerts
|

Association of Interferon-γ, Interleukin-10, and Tumor Necrosis Factor-α Gene Polymorphisms with Occurrence and Severity of Eales' Disease

Abstract: These data suggest that a low IL-10-expressing and high TNF-α-expressing genotype of the host can influence the occurrence and severity of outcome of ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…16 Recent findings, including our previous study, have found TNF-a promoter polymorphisms to be associated with several eye diseases like primary open-angle glaucoma, pseudoexfoliation glaucoma, and Eales. [25][26][27] It may be noted that the deviation from HWE of rs361525 observed among the PDR subjects but not among the controls is unlikely to be because of the population substructure. The likely cause of significant deviation of rs361525 from HWE among PDR subjects is because of significant association of specific genotypes/allele at this locus with the disease.…”
Section: Discussionmentioning
confidence: 99%
“…16 Recent findings, including our previous study, have found TNF-a promoter polymorphisms to be associated with several eye diseases like primary open-angle glaucoma, pseudoexfoliation glaucoma, and Eales. [25][26][27] It may be noted that the deviation from HWE of rs361525 observed among the PDR subjects but not among the controls is unlikely to be because of the population substructure. The likely cause of significant deviation of rs361525 from HWE among PDR subjects is because of significant association of specific genotypes/allele at this locus with the disease.…”
Section: Discussionmentioning
confidence: 99%
“…19 On the contrary, IL-10 is classically described as an anti-inflammatory and immunoregulatory factor by inhibiting T-cell immunity and TNF-α production. 17 However, it seemed not strong enough to counteract the effects of IL-6 and TNF-α in this patient. Overall, certain cytokines can contribute to the inflammation and immunomodulation of the retinal vessels, and may play a part of triggering factors in the development of FBA.…”
Section: Discussionmentioning
confidence: 73%
“…Besides the inflammatory retinal edema, vasodilation caused by vasculitis is another common symptom in uveitis patients. 32 Semiquantifiable scoring systems are available to evaluate the vessel size as a criterion for severity scores. Herein, we quantified the retinal vessel diameter as the second indicator.…”
Section: Discussionmentioning
confidence: 99%